Aplikasi Model Altman Z-Score Dalam Memprediksi Kebangkrutan Perusahaan Agro dan Marine - Sari, Dewi Maya; Mislinawati, Mislinawati (Universitas Teuku Umar, 2024)
This research aims to analyze the application of the Altman Z-Score bankruptcy model to test the financial health of agro-marine industry companies indexed on the Indonesian Stock Exchange. This research covers 23 agro- and marine-industry companies over a period of 3 years (2018–2020). Data analysis uses quantitative descriptive analysis methods. The results of the analysis identified three main categories, namely safe, gray (fairly safe), and distress (under pressure). These results demonstrate the diversity of financial conditions within this sector and highlight the importance of bankruptcy analysis for managing financial risk. The results of this research have implications for investors' caution factors in making investment decisions.